2012
DOI: 10.1007/s10695-012-9721-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical and handling exposure on fatty acids, oxidative stress and morphological welfare indicators in gilt-head sea bream (Sparus aurata)

Abstract: This work investigates the changes in the morphological traits, body composition, body fat and oxidative stress of Sparus aurata under two stress conditions: a low weekly exposure to the pesticide Diuron and chronic handling stress. The fish exposed to handling stress showed lower values in the morphological traits and perivisceral fat, whereas chemical stress induced a decrease in the percentage of muscle and carcase and an increase in the percentage of spleen and hepatosomatic index. The two stress situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In Flathead mullet, our previous research (Fazio et al 2014) showed a positive relationship between TOS and TAC following different storage times of serum. Other authors (Sanchez-Muros et al 2013) showed a correlation between ROS and FRAP in different tissues (liver, muscle, digestive and gill) in unstressed S. aurata; this positive trend disappears in the stressed fish and may even become a negative trend in the organs of the fish. Correlative relationships between pro-oxidative parameters and antioxidant enzyme activities also conform to what is anticipated if the peroxidation process is subsequent to the exhaustion of the antioxidant defence system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In Flathead mullet, our previous research (Fazio et al 2014) showed a positive relationship between TOS and TAC following different storage times of serum. Other authors (Sanchez-Muros et al 2013) showed a correlation between ROS and FRAP in different tissues (liver, muscle, digestive and gill) in unstressed S. aurata; this positive trend disappears in the stressed fish and may even become a negative trend in the organs of the fish. Correlative relationships between pro-oxidative parameters and antioxidant enzyme activities also conform to what is anticipated if the peroxidation process is subsequent to the exhaustion of the antioxidant defence system.…”
Section: Discussionmentioning
confidence: 87%
“…In fish, some authors showed that oxidation products and antioxidant defences were correlated in the muscle of several estuarine fish species (Madeira et al 2013). Particularly, a correlation between ROS and FRAP (ferric reducing antioxidant potential) in different tissues (liver, muscle, digestive and gill) has been shown in Sparus aurata (Sanchez-Muros et al 2013). Other researchers (Fazio et al 2014) have shown a positive relationship between total oxidant status (TOS) and total antioxidant capacity (TAC) in serum from Flathead mullet analysed after different periods of storage (2, 24, 48 and 72 h) at 4 °C.…”
mentioning
confidence: 94%
“…a), indicate that the probable cause is the higher level of PUFAs and HUFAs, indicating a high response capacity of these two organs, as it has been described under multiple stress conditions (Sánchez‐Muros et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Environmental stressors interfere with sub-organismal constituents such as cells and tissues, therefore, biomolecular and biochemical levels are sensitive and quick-responding indicators to stressors (Adams and Greeley, 2000). Indeed, alteration in FA composition is a sensitive early warning bio-indicator of stress, as evidenced by numerous studies (Gonç alves et al, 2012b(Gonç alves et al, , 2016Maazouzi et al, 2008;Ramírez et al, 2013;Sánchez-Muros et al, 2013).…”
Section: Introductionmentioning
confidence: 99%